Electrochemical Sensing Strategies for Synthetic Orange Dyes - Wu, Dihua; Zhu, Jiangwei; Zheng, Yuhong; Fu, Li (Molecules (Basel, Switzerland), 2024)
This review explores electrochemical sensing strategies for synthetic orange dyes, addressing the growing need for sensitive and selective detection methods in various industries. We examine the fundamental principles underlying the electrochemical detection of these compounds, focusing on their redox behavior and interaction with electrode surfaces. The review covers a range of sensor designs, from unmodified electrodes to advanced nanomaterial-based platforms. Chemically modified electrodes incorporating polymers and molecularly imprinted polymers are discussed for their enhanced selectivity. Particular attention is given to nanomaterial-based sensors, including those utilizing carbon nanotubes, graphene derivatives, and metal nanoparticles, which have demonstrated exceptional sensitivity and wide linear ranges. The potential of biological-based approaches, such as DNA interaction sensors and immunosensors, is also evaluated. Current challenges in the field are addressed, including matrix effects in complex samples and long-term stability issues. Emerging trends are highlighted, including the development of multi-modal sensing platforms and the integration of artificial intelligence for data analysis. The review concludes by discussing the commercial potential of these sensors in food safety, environmental monitoring, and smart packaging applications, emphasizing their importance in ensuring the safe use of synthetic orange dyes across industries.